2022
DOI: 10.3389/fcell.2022.824851
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Vasculature: Current Aspects and Long-Term Consequences

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was first identified in December 2019 as a novel respiratory pathogen and is the causative agent of Corona Virus disease 2019 (COVID-19). Early on during this pandemic, it became apparent that SARS-CoV-2 was not only restricted to infecting the respiratory tract, but the virus was also found in other tissues, including the vasculature. Individuals with underlying pre-existing co-morbidities like diabetes and hypertension have been more prone to devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 307 publications
(410 reference statements)
1
42
0
2
Order By: Relevance
“…In addition, in humans challenged with influenza virus increased levels of C3a and C5a were detected in the upper respiratory tract ( 47 ), intriguingly most often during the recovery phase rather than the acute infection phase, presumably concomitant with when antibody responses are established. Other effects of complement activation may include the destruction of host cells due to the formation of the membrane attack complex (MAC) and the activation of the coagulation cascade and effects on the vasculature ( 38 , 46 , 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in humans challenged with influenza virus increased levels of C3a and C5a were detected in the upper respiratory tract ( 47 ), intriguingly most often during the recovery phase rather than the acute infection phase, presumably concomitant with when antibody responses are established. Other effects of complement activation may include the destruction of host cells due to the formation of the membrane attack complex (MAC) and the activation of the coagulation cascade and effects on the vasculature ( 38 , 46 , 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we inferred that associating Vitamin C with other nutraceuticals playing similar actions, like L-Arginine, could be useful. On these grounds, considering that both L-Arginine and Vitamin C are known to improve endothelial function and reduce vascular permeability during infectious disorders 75 , 83 , 84 , 85 , 86 , and based on the emerging role of vascular permeability in Long-COVID 87 , 88 , we designed a study to assess the effects of a combination of L-Arginine and Vitamin C in Long-COVID.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has affected nearly 80 million Americans to date, many of whom are young adults without preexisting conditions ( 1 ). Although initially thought to be a respiratory disease, it is increasingly recognized that COVID-19 induces vascular dysfunction in persons who become infected ( 2 ). Indeed, we and others have previously shown that COVID-19 resulted in reduced endothelial function indicated by decreased flow-mediated dilation (FMD) ( 3 5 ), impaired microvascular reactivity (i.e., blunted reactive hyperemia) ( 3 , 4 ), and increased arterial stiffness ( 3 , 6 ).…”
Section: Introductionmentioning
confidence: 99%